socio-demographical and psychiatric characteristics of donors candidates applied to a transplantation centre - İzci, Filiz; Fındıklı, Ebru; Camkurt, Mehmet Akif; Akın, Barış (Journal of Dependence, 2016)
Objective: Alcohol and drug use may affect the course and the treatment of any disease as organ transplantation which requires a long-time treatment process. In this study, it was aimed to evaluate the psychiatric status, socio-demographical characteristics and frequency of alcohol-drug use of organ donor candidates before the transplantation process.Method: The study was conducted in the Şişli Florence Nightingale Hospital between January 2015 and May 2015. The participants composed of 68 volunteers between the ages of 18 and 65, who were applied as a donor candidate evaluated in terms of psychiatric disorders whether they can be organ donors or not. Socio-demographic form and SCID-I were applied to all participants.Results: Mean age was 42.12±12.7, % 44.1 (n=30) were male and % 55.9 (n=38) were female. According to the relationship to the recipient and donor candidates; % 47.1 of individuals were first-degree relatives, % 25 were spouses, % 27.9 were friends or distant relatives. % 16.2 of the individuals had previous psychiatric medication use and % 26.5 had a psychiatric medication use in their families. % 27.9 of the participants were smoking. Alcohol uses were as follows: % 1.5 every day, % 11.8 once a week, % 16.2 once a month. None of the participants had drug use or abuse.Conclusion: In our study, it was found thatthefrequencyofpsychiatricdisordersand alcohol use among organ donor candidates that applied to the transplantation center were higher than expected. Because live organ donors are more frequent in Turkey when compared to other countries and the donors are usually a relative, the closer relatedness between patients and donors is important in terms of relationships. In addition, it should be kept in mind that the frequency of psychiatric disorders is frequent among organ donor candidates.
Keywords: Organ transplant; socio-demographic characteristics; alcohol and drug use; donor candidate